Efficient side lobe level reduction technique for planar antenna arrays - Shimaa M Amer; Ahmed M. Elkhawaga; Ashraf A.M. Khalaf; Amr H. Hussein (Results in Engineering)
This paper presents a novel array synthesis technique based on the virtual antenna array (VAA) concept for side lobe level (SLL) reduction of uniform planar antenna arrays (UPAA). The VAA decomposes the (M×N) UPAA into vertical and horizontal uniform linear antenna arrays (V–ULAA and H–ULAA) consisting of M and N antenna elements, respectively. The V-ULAA and H-ULAA are positioned perpendicularly and closely enough apart to form a new (M+N) virtual UPAA. Consequently, the number of antenna elements is significantly reduced, which in turn minimizes the computational complexity and signal processing time required to synthesize the desired radiation pattern. Therefore, instead of reducing the SLL of the entire UPAA, we simply reduce the SLL of each ULAA using the well-known hybrid Method of Moments/Genetic Algorithm (MoM/GA) array synthesis technique, which adjusts both the excitation coefficients and element spacings to achieve low SLL. The MoM/GA results in non-uniform V-LAA and H-LAA having two non-uniform excitation vectors AV and AH, respectively, and much lower SLLs than the corresponding V-ULAA and H-ULAA. Finally, the synthesized excitation vectors AV and AH are used to synthesize either the virtual (M+N) planar antenna array (V-PAA) or the physical (M×N)PAA with more than two-fold reductions in the SLL.